The educational philosophy of Luis Emilio Recabarren and its influence on the Chilean Working Class and its class struggle strategies - María Alicia Vetter (Adult Education Research Conference, 2006)
This paper documents the major class struggles of the Chilean working class during the “Nitrate Era”. It highlights the leadership of Luis Emilio Recabarren, who understood working-class education as a strategy for power.
Keywords: Workers’ education; Luis Emilio Recabarren; class struggle